Biomonitoring of lead (Pb) toxicity through aquatic macrophyte Eichhornia crassipes - Gupta, Kiran (International Journal of Environment, 2014)
A study was performed for biomonitoring the toxicity of lead (Pb) in water hyacinth (Eichhornia crassipes). To assess phytotoxic response of the plant against Pb chlorophyll content, protein content and NR activity has been observed while genotoxiocity was analyzed by study of mitotic index and micronuclei (MNCs) as genotoxic end point. For this purpose, Plants of Eichhornia crassipes were exposed to various concentrations of Pb (0.0, 1, 2, 4 and 8 ppm) for 2 and 7 days durations. Pb induced phytotoxicity was evident by reduction in chlorophyll content, protein content and nitrate reductase activity (NR activity). All aforesaid parameters decreased in dose-duration dependent manner. Pb treatment also led to dose-duration dependent inhibition of mitotic index (MI) and induction of micronuclei in root meristematic cells of E. crassipes. Decline in MI reflects cytotoxicity that directly affects root growth and elongation. Pb may cause cell death, which may appear as decline in MI. Micronucleus induction involving the mitotic spindle and consequent production of laggard chromosomes during anaphase and loss of a complete chromosome. The present investigations revealed that E. crassipes exposed to Pb experienced phyto-genotoxicity, therefore it can be utilized as biomonitoring tool for toxicity of Pb assessment. DOI: http://dx.doi.org/10.3126/ije.v3i2.10500 International Journal of the Environment Vol.3(2) 2014: 12-19